Association of bone mineral density and diabetic retinopathy in diabetic subjects: the 2008–2011 Korea National Health and Nutrition Examination Survey. Issue 7 (July 2016) - Lim, Y.; Chun, S.; Lee, J.; Baek, K.; Lee, W.; Yim, H.-W.; Kang, M.-I.
Abstract Summary Because diabetic retinopathy increases fracture risk, we studied the association between bone mineral density (BMD) and diabetic retinopathy in a nationally representative sample. A significant association between the presence of diabetic retinopathy and low BMD was observed. Therefore, diabetic retinopathy might be considered as a marker of low BMD. Introduction Several diabetic complications, including nephropathy, retinopathy, and peripheral neuropathy, are associated with a higher fracture risk in diabetic subjects. However, in contrast to diabetic nephropathy and peripheral neuropathy, which are associated with low bone mineral density (BMD), little is known about the association between BMD and diabetic retinopathy. The aim of the present study was to determine whether the prevalence of diabetic retinopathy is associated with BMD. Methods This cross-sectional study included a nationally representative sample consisting of 4357 men aged 50 years and older and 4392 postmenopausal women who participated in the Korea National Health and Nutritional Examination Survey (KNHANES) from 2008 to 2011 and underwent BMD measurement by dual-energy X-ray absorptiometry (DXA) and diabetic retinopathy assessments using seven standard gradable photographs. Results The diabetic women with retinopathy had lower mean BMD at all measured sites than those without retinopathy, although the BMD difference between the two groups was small (3–5 %). In addition, the diabetic women with retinopathy were 2.27 times more likely to have osteoporosis following adjustments for all clinically relevant covariates. However, the prevalence of diabetes mellitus (DM) or diabetic retinopathy was not associated with the prevalence of osteoporosis in men. Conclusions This study has shown that the presence of diabetic retinopathy is significantly associated with a reduced BMD and increased prevalence of osteoporosis in diabetic women.